Porcine Plasmacytoid Dendritic Cells Are Unique in Their Expression of a Functional NKp46 Receptor - Mair, Kerstin H.; Stadler, Maria; Razavi, Mahsa Adib; Saalmüller, Armin; Gerner, Wilhelm (Frontiers in Immunology, 2022)
The activating receptor NKp46 shows a unique expression pattern on porcine leukocytes. We showed already that in swine not all NK cells express NKp46 and that CD3+NKp46+ lymphocytes form a T-cell subset with unique functional properties. Here we demonstrate the expression of NKp46 on CD4highCD14-CD172a+ porcine plasmacytoid dendritic cells (pDCs). Multi-color flow cytometry analyses revealed that the vast majority of porcine pDCs (94.2 % ± 4) express NKp46 ex vivo and have an increased expression on the single-cell level compared to NK cells. FSC/SSChighCD4highNKp46+ cells produced high levels of IFN-α after CpG ODN 2216 stimulation, a hallmark of pDC function. Following receptor triggering with plate-bound monoclonal antibodies against NKp46, phosphorylation of signaling molecules downstream of NKp46 was analyzed in pDCs and NK cells. Comparable to NK cells, NKp46 triggering led to an up-regulation of the phosphorylated ribosomal protein S6 (pS6) in pDCs, indicating an active signaling pathway of NKp46 in porcine pDCs. Nevertheless, a defined effector function of the NK-associated receptor on porcine pDCs could not be demonstrated yet. NKp46-mediated cytotoxicity, as shown for NK cells, does not seem to occur, as NKp46+ pDCs did not express perforin. Yet, NKp46 triggering seems to contribute to cytokine production in porcine pDCs, as induction of TNF-α was observed in a small pDC subset after NKp46 cross-linking. To our knowledge this is the first report on NKp46 expression on pDCs in a mammalian species, showing that this receptor contributes to pDC activation and function.